Lactase persistence, milk intake, hip fracture and bone mineral density: a study of 97 811 Danish individuals and a meta‐analysis. (10th April 2018) - Bergholdt, H. K. M.; Larsen, M. K.; Varbo, A.; Nordestgaard, B. G.; Ellervik, C.
Abstract: Background: Whether a causal relationship exists between milk intake and reduced risk of fractures is unclear. Objectives: We tested the hypothesis that genetically determined milk intake reduces the risk of fractures and increases bone mineral density (BMD). Methods: We investigated the association between milk intake, LCT‐13910 C/T (rs4988235), which is associated with lactase persistence ( TT/TC ) in Northern Europeans, and hip fractures in three Danish prospective studies ( N = 97 811, age ≥20 years). We added meta‐analyses of LCT‐13910 and fractures and BMD from five published Northern European population studies. Results: In the Danish studies, the adjusted hazard ratio (HR) for hip fracture per one glass per week higher milk intake was 1.00 (95% CI: 0.99–1.01). The per T ‐allele milk intake was 0.58 (0.49–0.68) glasses per week, but HR was 1.01 (0.94–1.09) for hip fracture. In meta‐analyses of Danish studies with published Northern European population studies, the random effects odds ratio for any fracture was 0.86 (0.61–1.21; I 2 = 73%) for TT vs . CC and 0.90 (0.68–1.21; I 2 = 63%) for TC vs . CC . The standardized mean difference in femoral neck BMD was 0.10 (0.02–0.18; I 2 = 0%) g cm −2 for TT vs . CC and 0.06 (−0.04 to 0.17; I 2 = 17%) g cm −2 for TC vs . CC . There were no differences in lumbar spine or total hip BMD comparing TT or TC with CC . Conclusion: Genetically lifelong lactase persistence with high milk intake was not associated with hip fracture in Danish population‐based cohorts. A meta‐analysis combining Danish studies with published Northern European population studies also showed that lactase persistence was not associated with fracture risk. Genetic lactase persistence was associated with a higher femoral neck BMD, but not lumbar spine or total hip BMD.